PERSEPSI MAHASISWA CALON GURU SEBAGAI PELAKU USAHA DALAM PENDIDIKAN KEWIRAUSAHAAN DI PERGURUAN TINGGI - Angga Rini, Titis; Syarifah Putri, Zahirotus; Hanisvana, Dinik; Anggun Luqmana, Annisa (Jurnal Muara Pendidikan, 2024)
Edupreneurship in higher education is aimed at introducing and developing student entrepreneurship. This research explored student teachers' perceptions of business behaviour in implementing edupreneurship. The study uses quantitative descriptive methods by extracting data through questionnaires and supporting documentation. This research began with a literature review, which was used as a basis for preparing research instruments for data mining, which was then continued in the final stage for data processing and concluding. The research results show prospective teacher students have a good perception (84.5%) of business interests, persistence and fighting power, business strategies, and their profession as entrepreneurial teachers or teacherpreneurs. This good perception is believed to provide positive affirmation to support better business behaviour, especially in the era of the Industrial Revolution. This perception can be a reference in developing entrepreneurship through entrepreneurship in higher education.